PBPK‐Based Prediction of Oliceridine Exposure in Breast Milk and Relative Infant Dose During the First 24 h After Cesarean Delivery - Yixi Ding; Ke Liu; Shuaishuai Zhang; Yanxu Zhang; Xin Tan; Weimin Xu (The Journal of Clinical Pharmacology, 2026)
Abstract Oliceridine is an intravenous opioid analgesic for postoperative pain control, but data on transfer into human milk and infant exposure during early breastfeeding remain limited. This study used a postpartum physiologically based pharmacokinetic (PBPK) framework to estimate oliceridine milk exposure and relative infant dose (RID) on postoperative Day 1 (0‐24 h) after cesarean delivery under a reconstructed patient‐controlled intravenous analgesia regimen. Maternal plasma exposure was simulated in PK‐Sim; milk exposure was extrapolated using an externally specified milk‐to‐plasma ratio (M/P). RID was calculated from mean milk concentration, infant milk intake, and the maternal weight‐normalized daily dose. An exposure scaling factor from an independent adult intravenous reference scenario was applied only as a post hoc proportional correction to RID. Morphine benchmarking assessed the physiological plausibility of the M/P extrapolation step, and a 4‐24 h temporal sensitivity check examined the influence of the initial accumulation phase. In the base case, maternal plasma AUC over 0‐24 h was 120.59 ng·h/mL; mean plasma and milk concentrations were both 5.025 ng/mL. The uncorrected model‐predicted RID was 0.375%, and the ESF‐corrected RID was 0.307%, both below the empirical 10% reference threshold. In one‐way sensitivity analysis, M/P and infant milk intake had greater effects on corrected RID than maternal body weight within the prespecified ranges. The maximum corrected RID was 0.818% in the two‐way scan and 1.235% under the prespecified high‐exposure scenario. These findings provide a preliminary, assumption‐bounded quantitative reference for modeled relative infant exposure under prespecified postoperative Day 1 extrapolation assumptions.